Difficult Psychiatric Consultations An Integrated Approach - Delgado, Sergio V.; Strawn, Jeffrey R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This innovative and important book describes a practical and clinically-relevant approach to the (3z(Bdifficult(3y (Bpsychiatric consultation. The authors systematically examine psychodynamic theories, family systems theories, and legal and ethical aspects of these consultations. Difficult Psychiatric Consultations: An Integrated Approach is unique compared to most psychiatric texts, in that it weaves traditional concepts in understanding a person and their family with contemporary developmental and relational concepts. The importance of these concepts, when applied to the study of the complexities and the interplay between patients, treatment teams and patients$1 (Bfamilies in today$1 (Bs medical centers, is brought to life through rich, real-life clinical examples. These powerful clinical vignettes allow the reader to put himself in the psychiatric consultant$1 (Bs shoes as he navigates practical interventions to improve the outcomes of (3z(Bdifficult(3y (Bconsultations. To that end, the authors provide tables to outline pre and post diagnosis observable patterns of the parties involved in the psychiatric consultation. This book has much to offer to general psychiatrists, child and adolescent psychiatrists, psychiatric residents, psychologists, nurse practitioners and social workers.s
Introduction -- Integrating theoretical paradigms -- The patient: Cognitive Functioning -- Temperament -- The Family -- Family System Theory -- Family System Concepts -- Genograms and Family Mapping -- The Family in child and adolescent psychiatry -- The treatment team: Evolution of the team -- Anatomy of the team -- Countertransference in the psychiatric consultant and the treatment team -- Ethics and Medisocial issues -- The culture -- A working definition of culture -- Culture Shock -- Mental Health across cultures -- Working with interpreters -- Culture in DSM IV and DSM V -- The clinical presentation -- Presentations -- Preparation of presentations.
Keywords: Medicine; Psychiatry; Psychotherapy; Philosophy (General).; Medicine & Public Health; Psychiatry; Psychology, general; Medicine/Public Health, general; Psychotherapy